EKSPEKTASI DAN PERSEPSI WISATAWAN TERHADAP GASTRONOMI MAKANAN BALI - Sri Sadjuni, Ni Luh Gde (JURNAL KEPARIWISATAAN, 2010)
The purpose of this research is: to find out the types of Balinese Food product to fulfill the desires and needs of tourists; to identify the factors that effect the perception and expectation; to know the perception and expectation of tourists about Balinese Gastronomy. The data were collected by administering a set of questionnaire to foreign tourists by applying non-probability, Accidental sampling. Some experts in the field of culinary is interviewed and also direct observation. The variable which is part of perceptions and expectations judgment about  Balinese Food Gastronomy consists of 13 items, which is grouped into five factors: 1) Food Quality; 2) Portion and Food Prices; 3) Temperature and Service Quality; 4) Presentation and Emotional Value; 5) Cleanliness and Accessibility to get the food. The analysis technic used in this research is discriminant analysis, correlation analysis and factor analysis. The result of the analysis shows two sub factors forming that has significant perception judgment component to its expectation which consist of one sub factor. The two sub correlation analysis and factor analysis. The result of the analysis shows two sub factors forming that has significant perception judgement component to its expectation which consist of one sub factor. The two sub factors perceptions are